The link between ankylosing spondylitis and oral health conditions: two nested case-control studies using data of the UK Biobank - Hadeel Mohammed Abbood; Ejaz Pathan; George P. Cherukara (University of São Paulo, 2018)
Abstract Ankylosing Spondylitis (AS) is an inflammatory rheumatic disease that affects the axial skeleton and the sacroiliac joints. Recent studies investigated the link between AS and oral diseases, particularly periodontitis. Others suggested that periodontitis may have a role in the pathogenesis of rheumatic diseases. Objective: The aim of this study is to investigate the association between AS and oral conditions. Material and Methods: This research was conducted using the UK Biobank Resource under Application Number 26307. The UK Biobank recruited around 500000 participants throughout Great Britain. Clinical records were available for 2734 participants. Two case-control studies were conducted based on whether AS was self-reported or clinically diagnosed. Oral conditions were identified using self-reported reports of oral ulcers, painful gums, bleeding gums, loose teeth, toothache, and dentures. The association between AS and oral conditions was assessed using logistic regression adjusted for age, gender, educational level, smoking status, alcohol consumption, and body mass index. Results: A total of 1307 cases and 491503 control participants were eligible for the self-reported AS study. The mean age was 58 years for the cases [7.5 standard deviation (SD)] and 57 years for the control groups (8.1 SD). Also, 37.1% of the cases and 54.2% of the control participants were females. Among the oral conditions, only oral ulcers were strongly associated with AS [1.57 adjusted odds ratio (OR); 95% confidence interval (CI) 1.31 to 1.88]. For the study of clinically diagnosed AS, 153 cases and 490351 control participants were identified. The mean age for both cases and control groups was 57 years; 7.6 SD for the cases and 8.1 for the control group. Females corresponded to 26.1% of the cases, and 54.2% of the control participants. Clinically diagnosed AS was associated with self-reported oral ulcers (2.17 adjusted OR; 95% CI 1.33 to 3.53). Conclusion: Self-reported and clinically diagnosed AS populations have increased risk of reporting oral ulcers. Further investigations are required to assess the link between a specific type of oral condition and AS.